Distinguishing drought resistance strategies and identifying indicator traits of Platycladus orientalis and Broussonetia papyrifera - Yao, Kai; Tu, Chunxiu; Zhang, Aoli; Zeng, Zhaoxia; Yang, Yang (Frontiers in Plant Science, 2025)
Tree species adopt diverse drought resistance strategies, which are crucial for the ability of karst vegetation to adapt to drought stress. However, our understanding of how to differentiate these strategies remains limited, particularly with respect to identifying indicator traits that can accurately distinguish the drought resistance strategies used by different species. In this study, we use principal component analysis based on functional traits to distinguish the drought resistance strategies of Platycladus orientalis and Broussonetia papyrifera; we identify key indicator traits reflecting differences in drought resistance strategies by analyzing the correlations of the same traits across different plant species. Most importantly, in this study, stomatal transpiration efficiency is proposed as a novel trait. Principal component analysis based on functional traits can distinguish plant drought resistance strategies. A correlation analysis of the indicators revealed that 2,2-diphenyl-picrylhydrazyl radical-scavenging activity, Δcrown width, stomatal transpiration efficiency, and water use efficiency can serve as critical markers to differentiate the drought resistance strategies of plants. Notably, the stomatal transpiration efficiency of P. orientalis and B. papyrifera exhibited entirely opposite trends under drought stress (r = -0.38); however, investigations of additional tree species are needed to further verify the reliability of stomatal transpiration efficiency as an indicator of different plant drought resistance strategies. These findings improve our ability to effectively differentiate karst plant drought resistance strategies and understand the mechanisms involved.